Risk Analysis on Conceptual Design of Soekarno – Hatta International Airport Rail Link Project Using Value Engineering - Rahman, Herawati Zetha; Berawi, Mohammed Ali; Susilowati, Suci Indah; Miraj, Perdana; Petroceany, Jade S. (UI Scholars Hub, 2015)
The Soekarno-Hatta International Airport Rail Link (SHIARL) project is arguably one of the best solutions to reduce uncertainty in travel time and to improve accessibility to and from Soekarno-Hatta International Airport. Due to low feasibility assessments, the private sector is holding back on their investment for this mega project infrastructure; therefore, a comprehensive study is required to improve project return on investment attractiveness. This study mainly identifies major risks and mitigation strategies by combining Value Engineering (VE) and Risk Management (RM). Questionnaire surveys and risk analysis will be used to respond to the research objectives and the analysis will be presented in the methodology section. The VE process produces additional functions as the integration of the MRT line, the Flood Control Tunnel (PRASTI), the Rail Link and infrastructure utilities which are expected not only to solve transportation problems, but also flood control problems in Jakarta. On the other hand, the RM process points out route selection error as a major risk that has to be mitigated for a successful project.